Resolução de problemas e representações múltiplas no ensino de sistemas de equações polimoniais do 1º Grau com duas incógnitas - Silva, Juscelino de Araújo (2019)
This work highlights the potentialities of problem solving, allied to the use of multiple representation, in the teaching of systems of first degree polynomial equations with two unknowns. For that, starting from a bibliographic survey on researches on Algebra teaching, more specifically, on what refers to the teaching of systems of first degree polynomial equations with two unknowns, in Mathematics of Basic Education, it was decided to work with the use of problem solving allied to ideas about multiple representations, according to Goldin and Shteingold (2001) and Friedlander and Tabach (2001). In order to reach the proposed objective, the research, of qualitative feature, was performed in a municipal school in the city of Mari, Paraíba state, with an 8th grade group, making use of the Problem Solving methodology (PS), especially based on the contributions of Andrade, C. and Onuchic (2017). By the end of the entire experience, and with data collected through a field journal and records made by students, it was observed that the moments of plenary, consensus, and content formalization of the Problem Solving methodology were greatly valuable for the students’ learning. It was also verified the necessity of listening to the students when they orally expose their verbal representations in relation to what they understood, in order to better comprehend their written records both in numerical, algebraic or graphic form, and then perceiving if they managed to assimilate the taught ideas. On the other hand, there is still the necessity of a further and better work of the addition and substitution methods, as well as the use of graphic representations.